Single-layer MoS2 solid-state nanopores for coarse-grained sequencing of proteins - Urquiola Hernández, Andreina; Delarue, Patrice; Guyeux, Christophe; Nicolaï, Adrien; Senet, Patrick (Frontiers in Nanotechnology, 2023)
Proteins are essential biological molecules to use as biomarkers for early disease diagnosis.Therefore, their detection is crucial and, in recent years, protein sequencing has become one of the most promising technique. In particular, Solid-State Nanopores (SSNs) are powerful platforms for single biological molecule sensing without any labeling and with high sensitivity. Atomically thin two-dimensional (2D) materials with nanometer-sized pores, such as single-layer MoS 2 , represent the ideal SSN because of their ultimate thinness. Despite the benefits they offer, their use for protein sequencing applications remains very challenging since the fast translocation speed provides short observation time per single molecule. In this work, we performed extensive Molecular Dynamics simulations of the translocation of the twenty proteinogenic amino acids through single-layer MoS 2 nanopores. From ionic current traces, we characterized peptideinduced blockade levels of current and duration for each of the twenty natural amino acids. Using clustering techniques, we demonstrate that positively and negatively charged amino acids present singular fingerprints and can be visually distinguished from the neutral amino acids. Furthermore, we demonstrate that this information would be sufficient to identify proteins using coarse-grained sequencing technique made of only three amino-acid categories depending on their charge. Therefore, single-layer MoS 2 nanopores have a great potential as sensors for the identification of biomarkers.